Information And Communication Technology: Status Quo Vs Development Directions In Military Applications - Bartlomiej TEREBINSKI (Communications of International Proceedings, 2022)
The paper's author highlights the significance of communication in the contemporary operations of the armed forces and the role of military communication in commanding combat formation elements. The author concludes that any attempt to disturb commanding, such as interfering in the information channel functions (including those based on engineering communication means), will trigger a chain reaction initiating, destabilising the operation of all combat formation elements, consequently jeopardising or even preventing any operations. At present, information is a strategic resource indispensable for taking optimum decisions and striving towards information advantage is a prerequisite for military operation success. The communication system ensures the capability of information collecting, storing, processing, and distribution to maintain uninterrupted information flow. This paper attempts to answer the following question: What is the modern military communication system like, and how should it be organised in the future to ensure effective combat commanding?
Keywords: communication and IT; communication system; military communication system; telecommunications.